STANDARDIZATION OF SYSTEMS, COMPLEXES AND MEANS OF CRYPTOGRAPHIC PROTECTION OF INFORMATION FOR APPLICATION IN POSTQUANTUM ENVIRONMENT - Korchenko, Anna; Ivanchenko, Yevheniya; Koshkina, Natalia; Kuznetsov, Oleksandr; Kachko, Olena; Potiy , Oleksandr; Onoprienko, Viktor; Bobukh , Vsevolod (Ukrainian Information Security Research Journal, 2023)
Cryptographic information protection (CRC) is an important component of information security of the state, directly related to overcoming modern problems and challenges in the cyberspace of Ukraine, new threats to information security in critical infrastructures in defense and security, industry, banking, economy, etc. Particularly dangerous in this sense are the new risks associated with the development and rapid implementation of modern and advanced information technologies that can radically change the architecture of information systems, existing paradigms, stable principles of construction and mathematical foundations of modern CCI tools. In particular, the emergence and rapid improvement of new computing tools based on the principles and effects of quantum physics (so-called universal quantum computers) threatens the very existence of existing and standardized at the national and international levels mechanisms (protocols, algorithms and tools) asymmetric cryptography.